Keanekaragaman Plankton pada Kolam Bioflok - Yulan Hardias Putri; Hari Santoso; Ahmad Syauqi (Jurnal Ilmiah Biosaintropis (Bioscience -Tropic), 2020)
Aquatic fertility in biofloc ponds is very dependent on the presence of plankton, an organism that lives floating in aquatic ponds and plays an important role as a source of natural food. This research aim to analyze the abundance and diversity of plankton in biofloc pools fed with probiotics. This study uses survey methods in the form of observations, measurement of water parameters, plankton sampling in biofloc ponds that have been given probiotic treatment at a dose that has been determined by the farmer at a depth of 1m biofloc pool with a diameter of 2m. The statistical analyzed used is the T test to diversity differences in plankton abundance between morning, afternoon and evening. The results obtained as many as 10 genus of phytoplankton and 26 genus of phytoplankton, namely Class 6 Cyanophyceae genus including Synechococcus, Oscilatoria, Choococcus, Spirulina, Microcystis, Scytonema. Chlorophyceae class 6 genus namely Haematococcus, Chlorella, Stigeoclonium, Calodophora, Tetraedon, Pyrobotrys. Bacillariophyceae class 5 genus namely Navicula, Eunotia, Cartuicula, Melosira, Rhaicosphera. Class Trebouxiophyceae 2 genus namely Botryococcus, Dictyosphaerium. The genus Euglenoidea 1 is Euglena. Cryptophyceae class 1 genus is Rhodomonas. Class Charophyceae 2 genus Mougeotia and Cryptomonas. The Zygnematophyceae class contains the Closterium genus. The Cyanophyta class contains the Anacystis genus. The Chrysophyceae class contains Dinobryon genus. From the identification results found Zooplankton with 3 classes and 3 genus namely Branchiopoda class, namely the Holopedium genus. The Maxillopoda class is the Copepoda genus. The Monogononta class is the Ascomorpha genus. The statistical test results showed that the diversity in each test was significantly different. Keywords: Plankton, Probiotics, Biofloc ABSTRAK Kesuburan perairan di kolam bioflok sangat tergantung pada keberadaan plankton yang merupakan organisme yang hidup melayang di kolam perairan dan berperan penting sebagai sumber pakan alami. Penelitian ini bertujuan untuk menganalisa kelimpahan dan keragaman plankton di kolam bioflok yang diberi probiotik. Penelitian ini menggunakan metode survei berupa pengamatan, pengukuran parameter air, pengambilan sampel plankton pada kolam bioflok yang sudah di beri perlakuan probiotik dengan dosis yang telah di tentukan oleh petani tambak pada kedalaman kolam bioflok 1m dengan diameter 2m. Analisis statistik yang digunakan adalah uji-T untuk mengetahui perbedaan keanekaragaman plankton antara pagi, siang dan sore hari. Hasil penelitian mendapatkan fitoplankton sebanyak 10 kelas dan 26 genus fitoplankton, yaitu Kelas Cyanophyceae 6 genus meliputi Synechococcus, Oscilatoria, Choococcus, Spirulina, Microcystis, Scytonema. Kelas Chlorophyceae 6 genus yaitu Haematococcus, Chlorella, Stigeoclonium, Calodophora, Tetraedon, Pyrobotrys. Kelas Bacillariophyceae 5 genus yaitu Navicula, Eunotia, Cartuicula, Melosira, Rhaicosphera. Kelas Trebouxiophyceae 2 genus yaitu Botryococcus, Dictyosphaerium. Kelas Euglenoidea 1 genus yaitu Euglena. Kelas Cryptophyceae 1 genus yaitu Rhodomonas. Kelas Charophyceae 2 genus Mougeotia dan Cryptomonas. Kelas Zygnematophyceae terdapat genus Closterium. Kelas Cyanophyta terdapat genus Anacystis. Kelas Chrysophyceae terdapat genus Dinobryon. Dari hasil identifikasi ditemukan Zooplankton dengan 3 kelas dan 3 genus yaitu kelas Branchiopoda yaitu genus Holopedium. Kelas Maxillopoda yaitu genus Copepoda. Kelas Monogononta yaitu genus Ascomorpha. Hasil uji statistika menujukan keragaman plankton pada setiap ulangan berbeda nyata. Kata Kunci: Plankton, Probiotik, Bioflok